2008
DOI: 10.1097/cmr.0b013e32830e3936
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment with vindesine in comparison to observation alone in patients with metastasized melanoma after complete metastasectomy: a randomized multicenter trial of the German Dermatologic Cooperative Oncology Group

Abstract: To evaluate the efficacy and safety of vindesine in patients with metastatic melanoma after complete metastasectomy. One hundred and forty-two patients with metastatic spread to regional sites, lymph nodes, and distant sites after complete metastasectomy were randomized to receive either treatment with vindesine for 2 years or observation alone. Vindesine 3 mg/m intravenously was administered biweekly for the first 26 weeks following 3-week intervals for an additional 26 weeks and thereafter every 4 weeks for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
(21 reference statements)
0
12
0
3
Order By: Relevance
“…Another randomized study investigated the efficacy of vindesine versus observation in the adjuvant therapy of melanoma [357]. Unlike a prior retrospective trial [358], this analysis demonstrated no significant differences neither in recurrence-free nor in overall survival.…”
Section: Level Of Evidence 1amentioning
confidence: 68%
“…Another randomized study investigated the efficacy of vindesine versus observation in the adjuvant therapy of melanoma [357]. Unlike a prior retrospective trial [358], this analysis demonstrated no significant differences neither in recurrence-free nor in overall survival.…”
Section: Level Of Evidence 1amentioning
confidence: 68%
“…This survival advantage, as reported by Eigentler, is short of statistical significance (P=0.07). On the strength of this P value, the authors referring to our study [2] conclude that their randomized trial did not confirm earlier reports of beneficial effect of adjuvant vindesine and therefore cannot be recommended [1].…”
mentioning
confidence: 88%
“…The study of adjuvant vindesine for clinically apparent, resectable metastases from melanoma, reported by Eigentler et al [1] in the October 2008 issue of the journal, shows a discernible overall survival advantage, in favour of adjuvant vindesine versus observation. This survival advantage, as reported by Eigentler, is short of statistical significance (P=0.07).…”
mentioning
confidence: 95%
“…In einer randomisierten Studie der German Dermatologic Cooperative Oncology Group, in der Hochrisiko-Patienten mit metastasiertem Melanom nach kompletter Metastasektomie mit Vindesin behandelt oder beobachtet wurden, war der Vorteil der adjuvant chemotherapeutisch behandelten Patienten weder beim krankheitsfreien Überleben (p = 0,40) noch bei der 3-Jahres-Gesamtüberlebensrate (p = 0,07) statistisch signifikant [5]. Auch zahlreiche andere randomisierte Studien zeigten keine relevanten Vorteile einer adjuvanten Chemotherapie.…”
Section: Adjuvante Chemotherapieunclassified
“…Ob die Prognose durch Einsatz von pegyliertem Interferon alpha verbessert werden kann, ist derzeit noch unklar. In der Phase-III-Studie EADO, in der bei Patienten mit einer Tumordicke > 1, 5 Als obligater Standard akzeptiert ist die adjuvante Strahlentherapie zum Beispiel bei der brusterhaltenden Therapie des Mammakarzinoms. Eindeutig empfohlen wird eine Radiotherapie in der aktuellen S3-Leitlinie bei Patientinnen mit Mastektomie und > 3 befallenen axillären Lymphknoten (pN+) (Empfehlungsgrad 1); bei 1-3 befallenen Lymphknoten wird dagegen keine Empfehlung ausgesprochen (Empfehlungsgrad 0), obwohl verschiedene, allerdings ältere Studien auch in dieser Behandlungssituation einen Nutzen der adjuvanten Radiatio zeigten [14].…”
Section: Adjuvante Immuntherapienunclassified